Optimizing Market Growth Strategies in South Sulawesi: A Comprehensive Evaluation using AHP - PT MCM Case Study - Chandra Kurniawan; Pri Hermawan (Research Synergy Foundation, 2023)
The fluctuations in DC Makassar's financial performance indicate the presence of factors that hinder its growth and profitability. Understanding the root causes of these challenges is essential for developing effective solutions and optimizing the financial stability of the distribution center. This study uses the Analytic Hierarchy Process (AHP) method of Multi-Criteria Decision Making (MCDM) to improve market growth in South Sulawesi, concentrating on the instance of PT MCM, especially on the Makassar Distribution Centre. The objective is to identify potential market development strategies and assess their viability and efficacy in attaining PT MCM's growth objectives. Additionally, the study evaluates the potential hazards and difficulties associated with implementing each alternative strategy. The research methodology entails collecting pertinent data and conducting interviews with key stakeholders to identify the critical factors influencing South Sulawesi's market development. Financial, market development, human resources, and operations are the four primary dimensions that categorize these factors. The AHP method is then used to determine the relative weights and priorities of each criterion and alternative strategy through a thorough evaluation. The AHP alternative in this study was formed based on the results of qualitative internal and external analysis. Based on the findings, three alternative strategies are identified: Full Third-Party Distributor, Stand Still and Invest in Makassar Branch Development. PT MCM's optimal strategy is determined to be the development of the Makassar Branch through investment, as determined by the evaluation procedure. This business solution highlights the significance of investing in HR development and control, expanding the number of potential customers, and enhancing brand equity as key priorities for the Makassar Branch's success. Preventive measures and contingency plans are proposed to address prospective threats and challenges. Among these are optimizing operational processes, controlling accounts receivable, implementing recruitment strategies, supplying training and resources, and conducting internal audits. In summary, the research has practical implications for DC Makassar by providing actionable insights to address its financial challenges. Additionally, the implications extend to the distribution center industry as a whole, fostering learning and improvement in financial performance and strategic decision-making.